THE LORD OF THE FAIRY-TALE. THE POLISH RECEPTION OF THE USES OF ENCHANTMENT BY BRUNO BETTELHEIM - Bednarek, Magdalena (Porównania, 2018)
The paper presents the Polish reception of The Uses of Enchantment by Bruno Bettelheim. The influential work published in 1976 in the U.S. was part of the fairy-tale renaissance, a movement which took place first place in Germany and then in North America within academic practises as well as in literature, movie art, photography, etc. Due to its unique position on the Polish market, Danuta Danek’s translation of Bettelheim’s monography had had an even greater impact on the local research not only in the field of the fairy-tales’ interpretation, but in the humanities in general. In Poland in the last 30 years ideas from The Uses of Enchantment have been petrified, in spite of the fact that in the West Bettelheim’s book was discussed and even attacked. The paper examines several controversies over the The Uses of Enchantment which have arisen in the Western humanities voiced by such authorities in the field as Jack Zipes, Alan Dundes, Pierre Péju, Jacqueline Rose, Maria Tatar and Ruth Bottigheimer.